Knowledge, Attitude, and Nurses’ Practices in Diabetic Wound Care with Modern Dressing: A Study in the Wound Care Unit - Sakinah, Nurul; Sastria, Andi; Asriadi; Amanah, Indra (AACENDIKIA: Journal of Nursing, 2025)
Diabetes mellitus is a metabolic disease characterized by elevated blood glucose levels above the normal range. Diabetic foot ulcers are a condition in which wounds on the feet are accompanied by discharge of foul-smelling pus. Modern dressing is a wound care method that maintains a moist and closed environment to prevent wound dryness and accelerate the healing process. This study aimed to examine the relationship between knowledge and attitude and nurses’ practices in diabetic wound care using the modern dressing method. A quantitative study with a descriptive correlational design and a cross-sectional approach was conducted, involving 36 nurses working in the wound care unit at RSUD Sawerigading Palopo. Respondents were selected using purposive sampling. The results showed a significant relationship between nurses’ knowledge and attitudes and their practices in diabetic wound care using modern dressing techniques. It can be concluded that both knowledge and attitude are important factors influencing the effective implementation of modern dressing methods in diabetic wound care.